Separating preferences from endogenous effort and cognitive noise in observed decisions - Christian Belzil; Tomáš Jagelka (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We develop a micro-founded framework for accounting for individuals' effort and cognitive noise which confound estimates of preferences based on observed behavior. Using a largescale experimental dataset we estimate that failure to properly account for decision errors due to (rational) inattention on a more complex, but commonly used, task design biases estimates of risk aversion by 50% for the median individual. Effort propensities recovered from preference elicitation tasks generalize to other settings and predict performance on an OECD-sponsored achievement test used to make international comparisons. Furthermore, accounting for endogenous effort allows us to empirically reconcile competing models of discrete choice.
Keywords: C40; D91; 330; Preferences; risk preference; stochastic choice models; endogenous effort; cognitive noise; task complexity; experimental design